12-Crown-4 ether assisted in-situ grown perovskite crystals for ambient stable light emitting diodes. (May 2022) - Xiang, Ting; Li, Ting; Wang, Miaosheng; Zhang, Wei; Ahmadi, Mahshid; Wu, Xiaoyan; Xu, Tianfei; Xiao, Meiqin; Xu, Long; Chen, Ping
Abstract: It is always difficult to control the growth of crystals during the formation of multiple quantum wells (MQWs) in the quasi-2D perovskite light emitting diodes (PeLEDs). In this study, we introduce the 1, 4, 7, 10-tetraoxacyclododecane ether into the quasi-2D perovskite of PEA2 Csn-1 Pbn Br3n+1 to reduce the coordination rate between the phenethylamine bromide and the perovskite framework. As a result, Crown-ether assisted in-situ grown (CAIG) perovskite crystals (PCs) is grown with thick PbBr4 layers (n > 55) during the spin-coating. For the CAIG PCs, the generation of small n phases (n = 1, 2 and 3) are significantly suppressed, resulting in almost flat energy structure with the phases of n ≥ 4. The generation rate of the excited states of the n ≥ 4 remains ultra-fast within ~0.77 ps even without the MQWs structures; however the decay of excited states becomes much slower. The CAIG PCs film has lower trap density, therefore promoting the carrier mobility, carrier diffusion length and the photoluminescence quantum yield. The PeLEDs based on the CAIG PCs film achieves the maximum luminescence of ~27562 cd m −2 and the maximum external quantum efficiency (EQE) of ~16.1%. The half-lifetime of the luminescence and the EQE measured in the atmosphere (a relative humidity of ~52% at 27 ℃) are exceeding ~17 and 43 h, respectively. Hence, it can be recognized as the most ambient stable device based on the PEA2 Csn-1 Pbn Br3n+1 perovskite. Graphical Abstract: 12-Crown-4 ether assisted in-situ grown perovskite crystals with thick PbBr4 layers (n > 55), improving the performance and stability of perovskite LEDs. ga1 Highlights: The CAIG PCs are achieved by introducing the 12-Crown-4 into PEA2 Csn-1 Pbn Br3n+1 . The μe/h, LD and the PLQY are simultaneously improved with reduced ntrap . The CAIG device is the most ambient stable PeLEDs based on the PEA2 Csn-1 Pbn Br3n+1 .